2015
DOI: 10.1016/j.nicl.2015.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Negative symptoms in schizophrenia are associated with aberrant striato-cortical connectivity in a rewarded perceptual decision-making task

Abstract: BackgroundNegative symptoms in schizophrenia have been associated with structural and functional changes in the prefrontal cortex. They often persist after treatment with antipsychotic medication which targets, in particular, the ventral striatum (VS). As schizophrenia has been suggested to arise from dysfunctional connectivity between neural networks, it is possible that residual aberrant striato-cortical connectivity in medicated patients plays a role in enduring negative symptomology. The present study exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 65 publications
(104 reference statements)
2
12
0
Order By: Relevance
“…Our findings may be consistent with findings of disrupted hemispheric specialization 34 and decreased global connectivity of the caudate 35 as well as those demonstrating deficient striato-cortical connectivity in schizophrenia 363739 and altered caudate-cortical connectivity in subjects at high-risk for psychosis 37,40 . Although dysfunction 41 and dysconnectivity 42 of the (ventral) striatum may relate to negative symptoms, we failed to find such a relationship, although more work in this direction is warranted. Together with findings highlighting the role of striatal dopamine dysregulation in schizophrenia 1 , our results suggest that disruptions of striatal circuitry may plausibly mediate the deleterious effects of dopamine dysregulation on cortical processes involved in perception and cognition 4345 .…”
Section: Discussionmentioning
confidence: 56%
“…Our findings may be consistent with findings of disrupted hemispheric specialization 34 and decreased global connectivity of the caudate 35 as well as those demonstrating deficient striato-cortical connectivity in schizophrenia 363739 and altered caudate-cortical connectivity in subjects at high-risk for psychosis 37,40 . Although dysfunction 41 and dysconnectivity 42 of the (ventral) striatum may relate to negative symptoms, we failed to find such a relationship, although more work in this direction is warranted. Together with findings highlighting the role of striatal dopamine dysregulation in schizophrenia 1 , our results suggest that disruptions of striatal circuitry may plausibly mediate the deleterious effects of dopamine dysregulation on cortical processes involved in perception and cognition 4345 .…”
Section: Discussionmentioning
confidence: 56%
“…A prior study showed that patients with persistent negative symptoms following first‐episode psychosis had significantly reduced left amygdala and right hippocampal volumes . Severity of negative symptoms is also related to reduced gray and white matter volumes in the frontal cortex . A single photon emission computed tomography study found a negative correlation between negative symptom scores and prefrontal perfusion in schizophrenia .…”
Section: Discussionmentioning
confidence: 99%
“…A recent fMRI study that observed normal VS response, but abnormal striatal-cortical connectivity to motivational cues that was related to negative symptom severity in patients with schizophrenia, may support that hypothesis. 46 A more complete understanding of the etiology of apathy in schizophrenia will therefore require further investigation of the structural and functional integrity of subregions within the frontal-striatal circuitry, as well as functional connectivity of the circuitry.…”
Section: Discussionmentioning
confidence: 99%